The Transformation of Planning and Forecasting in Management Accounting: a Bibliometric Analysis of Global Literature from 1973 to 2025 - Rani Julia Pratiwi; Sari Ayu Imaniyah; Puji Handayani; Nurika Restuningdiah (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to map the evolution of literature related to planning and forecasting within the context of accounting management using a bibliometric approach. Employing a Systematic Literature Review (SLR) and bibliometric analysis based on data retrieved from the Scopus database between 1973 and 2025, the research identifies trends, knowledge structures, and both established and emerging themes in the field. A total of 55 relevant documents were analyzed using VOSviewer software through co-occurrence analysis, density visualization, and overlay visualization techniques. The findings reveal two major categories in the literature: well-established themes such as